Effects of spironolactone on atrial structural remodelling in a canine model of atrial fibrillation produced by prolonged atrial pacing - Zhao, J (Blackwell Publishing Ltd, 2010)
BACKGROUND AND PURPOSE: Suppression of the renin-angiotensin-aldosterone system can prevent atrial fibrillation (AF) by attenuating atrial structural remodelling but the role of aldosterone in AF prevention has not been investigated thoroughly. We explored whether the aldosterone antagonist, spironolactone, could improve atrial structural remodelling in long-term rapid pacing-induced AF. EXPERIMENTAL APPROACH: Three groups of dogs were used, sham-operated, control and spironolactone-treated groups. Dogs in the control and spironolactone groups had right atrial pacing for 6 weeks. The spironolactone group was given spironolactone 1 week before and during the atrial pacing. After 6 weeks of pacing, atrial structural and functional changes were assessed by echocardiography, haemodynamic parameters by cardiac catheterization, histopathological changes by light and electron microscopy and cardiomyocyte apoptosis by TUNEL. Caspase-3, Bcl-2, bax, calpain I, calpastatin, matrix metalloproteinase (MMP)-9 and tissue inhibitors of metalloproteinase (TIMP)-1 were analysed by immunohistochemistry and Western blotting. The inducibility and duration of AF were measured by atrial burst pacing. KEY RESULTS: After atrial pacing, the proportion of TUNEL positive cells, myolysis, atrial fibrosis and dilatation were all significantly increased and these changes were inhibited by spironolactone. Spironolactone treatment reversed the increased expression of caspase-3, bax, calpain I and MMP-9 and the decreased level of Bcl-2, calpastatin and TIMP-1, induced by chronic atrial pacing. Also spironolactone prevented the increased inducibility and duration of AF, induced by tachypacing. CONCLUSIONS AND IMPLICATIONS: Treatment with spironolactone prevented myocardial apoptosis, myolysis, atrial fibrosis and dilatation, suggesting a possible beneficial effect of aldosterone antagonism on atrial structural remodelling in AF. This article is commented on by Lendeckel et al., pp. 1581–1583 of this issue. To view this commentary visit http://dx.doi.org/10.1111/j.1476-5381.2010.00675.x